Research on Bridging the Information Gap of BIM of interoperability and integration in Facilities Management - Kutaiba, Azmeh; Kwok Chuen, Liu (My University, 2020)
Building Information Modeling (BIM) is a combination of technologies and human work practice in handling geometric and non-geometric information management over the whole life cycle of the construction project. BIM has already matured for implementation in the design and construction phase of a construction project. However, there is still a low rate of utilization of BIM in asset operation and maintenance in the industry. Even though there has been a lot of academic research to study how asset information in BIM can leverage the workflow and performance of Facilities management (FM), there is still only 10% of companies/projects that recognize the benefit of the usage of BIM in Facilities management. There is less research to study the challenges of information integration from BIM to operation and maintenance. So, the purpose of this report is to investigate 1.) What information is required for FM, 2.) What hindrances are there in terms of information integration from BIM to FM and, 3.) What improvements can be done to the integration process. This report is a qualitative study and is based on a literature review and interviews. The interviews, which were semi-structured, were deployed in order to explore the different perspectives regarding the issues about the BIM-FM information transfer and integration process. The interviewees were acting as architects, engineering consultants, and facilities managers from different construction companies in Sweden and Hong Kong. Their experience and opinions from the interview provide findings to form the base of the conclusion. The main findings of this study are discussed. One cause of the problem of information integration from the BIM model to FM is because there is a lack of standard information requirements and format in facilities management. Each practitioner provides asset specification and construction detail in BIM with the format under their preference and perception. Furthermore, the insufficient collaboration between each party, inactive engagement from facilities managers at earlier stages, and different levels of knowledge toward BIM usage in FM and benefit recognition are also hindrances to drive further development of information integration from BIM to FM. BIM enabled FM benefits cannot be fully recognized due to many challenges mentioned above. This study concludes by calling upon a holistic integration of people, processes, and technical change in order to reach better performance of information integration from BIM to FM
Keywords: BIM, Information gap, Facility management, operational stage, information integration.